2018
DOI: 10.1128/mbio.02010-17
|View full text |Cite
|
Sign up to set email alerts
|

Robust Phagocyte Recruitment Controls the Opportunistic Fungal Pathogen Mucor circinelloides in Innate Granulomas In Vivo

Abstract: Mucormycosis is an emerging fungal infection with extremely high mortality rates in patients with defects in their innate immune response, specifically in functions mediated through phagocytes. However, we currently have a limited understanding of the molecular and cellular interactions between these innate immune effectors and mucormycete spores during the early immune response. Here, the early events of innate immune recruitment in response to infection by Mucor circinelloides spores are modeled by a combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…Resting or swollen spores were co-incubated with J774A.1 macrophage-like cells, un-engulfed spores washed away, macrophages lysed, and spores tested for viability. Consistent with our previous observations and others, 40,41 macrophages did not kill phagocytosed dormant or swollen spores ( Figure 2a) . Further, macrophages showed a defect in phagosome acidification as measured by lysotracker staining following uptake of both live resting and pre-swollen spores, suggesting a defect in phagosome maturation ( Figure 2b ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Resting or swollen spores were co-incubated with J774A.1 macrophage-like cells, un-engulfed spores washed away, macrophages lysed, and spores tested for viability. Consistent with our previous observations and others, 40,41 macrophages did not kill phagocytosed dormant or swollen spores ( Figure 2a) . Further, macrophages showed a defect in phagosome acidification as measured by lysotracker staining following uptake of both live resting and pre-swollen spores, suggesting a defect in phagosome maturation ( Figure 2b ).…”
Section: Resultssupporting
confidence: 93%
“…We previously showed that the early stages of host-fungus interaction determine disease outcome in the zebrafish model of mucormycosis 41 . Our data suggest that successful control requires both 1) the presence of phagocytes at the site of infection within the first 24 hours and 2) the formation of a granuloma capable of killing spores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations